2017
DOI: 10.15381/rpb.v24i4.14063
|View full text |Cite
|
Sign up to set email alerts
|

Diferenciación morfológica de Carollia brevicauda y C. perspicillata (Chiroptera: Phyllostomidae) de Perú y Ecuador

Abstract: En el género Carollia, Carollia brevicauda y C. perspicillata son las especies más abundantes y ampliamente distribuidas del género en América del Sur, además de tener distribuciones casi complemente sobrepuestas. Debido a que estas especies son morfológicamente similares en algunas localidades son frecuentemente mal identificadas. El objetivo de este estudio fue determinar las diferencias morfológicas y morfométricas de C. brevicauda y C. perspicillata. para esto, se empleó un análisis morfológico detallado y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
1
13
0
2
Order By: Relevance
“…We also studied the distribution and the scoring of discrete morphological characters available in the literature for species of Carollia (e.g., Pine 1972, Solari and Baker 2006, Zurc and Velazco 2010, Ruelas 2017.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also studied the distribution and the scoring of discrete morphological characters available in the literature for species of Carollia (e.g., Pine 1972, Solari and Baker 2006, Zurc and Velazco 2010, Ruelas 2017.…”
Section: Methodsmentioning
confidence: 99%
“…Herein we studied specimens of Carollia from several regions of Brazil previously identified as C. benkeithi, C. brevicauda or C. perspicillata checking the consistency of the characters available in the literature traditionally used for their differentiation (e.g., Pine 1972, Lim and Engstrom 2001, Solari and Baker 2006, McLellan and Koopman 2008, Zurc and Velazco 2010, Ruelas 2017) and investigating the distribution of the Carollia species in Brazil.…”
Section: Character Variation and Taxonomy Of Short-tailed Fruit Bats mentioning
confidence: 99%
See 1 more Smart Citation
“…For the taxonomic determination, we followed taxonomic keys (Gardner 2008, Diaz et al 2016, revisions (Barquez et al 1999, Woodman & Timm 2006, Garbino et al 2012, Ruelas 2017, and the specimens of the MUSM collection for comparisons. The taxonomic nomenclature used by Pacheco et al (2009) was complemented with more recent taxonomic changes (Parlos et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Linear discriminant analysis has been used with other species of Phyllostomidae: for example Ruelas (2017) determined the main morphometric and skull characteristics of Carollia species in Peru, which were probably not well identified due to the use of controversial characteristics for their identification (this may be occurring for the species of Carollia in Honduras as well). Another example is Foltran Fialho (2009), who said that the main morphometric characteristic to identify Artibeus in Brazil is the forearm length, however, our results are more closely in accordance with Davis (1970), who indicated that forearm length is not a completely reliable indication for identifying all Central American members of Artibeus species.…”
Section: Discussionmentioning
confidence: 99%